Association Between Obstetric History and Urinary Incontinence in a Cohort of Resistance-Trained Women - Wikander L; Kirshbaum MN; Waheed N; Gahreman DE (Dove Medical Press, 2022)
Lolita Wikander,1 Marilynne N Kirshbaum,2 Nasreena Waheed,3 Daniel E Gahreman1,4 1College of Health and Human Sciences, Charles Darwin University, Darwin, Northern Territory, Australia; 2Research and Innovation, Charles Darwin University, Darwin, Northern Territory, Australia; 3College of Nursing and Midwifery, Charles Darwin University, Darwin, Northern Territory, Australia; 4Department of Sport, Exercise, Recreation, and Kinesiology, East Tennessee State University, Johnson City, TN, USACorrespondence: Lolita Wikander, College of Health and Human Sciences, Charles Darwin University, Darwin, Northern Territory, Australia, Tel +61 421314515, Fax +61 08 8946 6642, Email lolita.wikander@yahoo.comPurpose: Urinary incontinence has the potential to reduce participation in sport and exercise and diminish athletic performance. The purpose of this study was to explore the association between obstetric history and urinary incontinence in a cohort of resistance-trained women.Patients and Methods: This international, cross-sectional survey was completed by 1252 women competing in either powerlifting, weightlifting or CrossFit. The Incontinence Severity Index determined the severity of urinary incontinence.Results: Almost 43% of the participants experienced urinary incontinence in the threemonths prior to the study. The prevalence of urinary incontinence in this cohort according to mode of birth were: caesarean 42.6%, unassisted vaginal 59.3%, vacuum extraction 58.8%, forceps 60.3%, vaginal and caesarean births 66.2%, forceps and vacuum extraction 73.1%. The prevalence of urinary incontinence in the subgroup of women who had undergone urogenital surgery was 63.6%. Kendall's tau-b indicated that the correlation between ISI score and the number of births was strong and positive (τ = 0.25, p < 0.001).Conclusion: Our results suggest that both the number of births and mode of birth influenced the likelihood of urinary incontinence in resistance-trained women. Women who had experienced only caesarean births had the lowest likelihood of urinary incontinence, while women who had experienced both vaginal and caesarean births had the most severe and second highest likelihood of urinary incontinence. Women who had undergone urogenital surgery continued to experience a high likelihood of urinary incontinence.Keywords: strength training, resistance training, pelvic floor, pregnancy